Participatory Evaluation of Development Projects Contribution to Poverty Reduction in Northern Benin - Zoundji, Gérard C.; Zossou, Espérance; Vodouhè, Fifanou; Sackey, Charles Kwame; Bognonkpe, Gillette (European Journal of Sustainable Development, 2022)
This study analyzed the sustainable changes induced by the "Banikoara Millennium Village Project" on rural poverty reduction. Using the purposive sampling method, 126 household heads were selected from three project beneficiary villages and one non- project beneficiary village. Data was collected through focus group discussions and a structured questionnaire which were processed using descriptive statistics. The results showed that nearly 78% of the respondents have adopted the improved technologies of soil fertility, and yields have increased from 1.2 tons to 3.5 tons per hectare for rice, from 1.4 tons to 2.1 tons per hectare for maize, and from 1 ton to 1.6 tons per hectare for sorghum. We also found that that the project has contributed to decreasing poverty in terms of the achievements of socio-community infrastructures in the education, health and agricultural sectors, the capacity building of communities etc. Majority (85%) of the project beneficiary households consider their current economic living conditions better than the period before the project implementation. This project has a great impact on household food security and shortening the hunger season. However, the project achievements are still fragile and require an action for sustainability. This study suggests that development projects should actively involve the target beneficiaries starting from the needs assessment in particular and implementation to ensure its sustainability. Keywords: Development project, Millennium Villages, Impact evaluation, poverty reduction